Homothetic Preferences Revealed - Jan Heufer; Per Hjertstrand (Tinbergen Institute, 2017)
We propose a method to recover homothetic preferences from choice data with minor optimization or measurement errors. Our method allows for a more detailed graphical analysis to reveal subjects' preferences and to choose appropriate functional forms for parametric analysis. It can also be used to extend applications of the money metric function, such as parametric recoverability as introduced by Halevy et al. (2017). It can also improve nonparametric comparison of preferences as suggested by Heufer (2014).
Keywords: C14; C91; D11; D12; 330; Graphical Analysis; Homotheticity; Money Metric Utility; Recoverability; Revealed Preference